2018
DOI: 10.1089/neu.2017.5422
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Measured Using Masseter Area Predicts Early Mortality following Severe Traumatic Brain Injury

Abstract: Sarcopenia is strongly associated with poor outcomes and mortality following injury among the geriatric population. Diagnosis using psoas area is most common but may be unavailable given limited radiographic evaluation following low-impact injuries. Masseter area has recently been identified as an available alternative and associated with 2-year mortality following injury. We sought to validate this measure and its association with early mortality following severe traumatic brain injury (sTBI) using a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
3
18
1
Order By: Relevance
“…The mean MA in these sarcopenic patients was 281 mm 2 in men and 224 mm 2 in women, and they were at increased risk of 30 day mortality (80.0% vs. 50.6%) vs. those with greater MA. 15 This finding is in line with the current analyses, which showed an inverse association between MA and mortality, and suggests that there may be a different threshold for increased mortality according to sex. The present study was not powered to analyse sex differences and the association of MAavg with mortality persisted despite adjustment by sex.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The mean MA in these sarcopenic patients was 281 mm 2 in men and 224 mm 2 in women, and they were at increased risk of 30 day mortality (80.0% vs. 50.6%) vs. those with greater MA. 15 This finding is in line with the current analyses, which showed an inverse association between MA and mortality, and suggests that there may be a different threshold for increased mortality according to sex. The present study was not powered to analyse sex differences and the association of MAavg with mortality persisted despite adjustment by sex.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of an inverse relationship between MAavg and mortality concurs with previous studies which found that MA predicted mortality in elderly patients suffering blunt trauma 14 or traumatic brain injury, 15 and this in turn suggests that MA could be used as a surrogate for sarcopenia. As in the present study, the association was mostly not influenced by age, suggesting that despite correlating with age, MA provides independent prognostic value when predicting death after trauma or CEA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In HNC patients, the sarcopenia reflect not only the swallowing function but also the nutritional status [18]. The masticatory muscles were also revealed to be equally valid marker of sarcopenia in trauma patients [19,20]. However, the correlation between masticatory muscle and underlying sarcopenia has never been studied in HNC patients.…”
Section: Introductionmentioning
confidence: 99%